2018
DOI: 10.18203/2394-6040.ijcmph20183103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adequately iodised salt consumption in Telangana state, India

Abstract: Background: Salt used in the household is the most common way for iodine fortification to prevent the public health concerns of iodine deficiency disorders. The objective of the study was to assess household coverage with adequately iodized salt in Telangana State, India. Methods: Secondary data published in the District Level Household and Facility Survey-4 is analyzed. Results: Overall, 55.7 percent of the households were using cooking salt which was iodized at the recommended level of 15 ppm or more. Around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…[ 15 16 17 18 ] Contrary to other studies done in West Bengal and other states of India, where non iodized salt consumption constituted a significant proportion, the present study found no households consuming non iodized salt. [ 12 13 ] An improved access to iodized salt of this deprived and poor section of the community is evident from this study, which may be attributed to continued efforts under NIDDCP to provide iodized packet salt at affordable price and a stringent ban on sell of non-iodized loose salt; however the findings also hint that only 'access to iodized salt' is not sufficient to maintain a good level of iodization at consumption.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[ 15 16 17 18 ] Contrary to other studies done in West Bengal and other states of India, where non iodized salt consumption constituted a significant proportion, the present study found no households consuming non iodized salt. [ 12 13 ] An improved access to iodized salt of this deprived and poor section of the community is evident from this study, which may be attributed to continued efforts under NIDDCP to provide iodized packet salt at affordable price and a stringent ban on sell of non-iodized loose salt; however the findings also hint that only 'access to iodized salt' is not sufficient to maintain a good level of iodization at consumption.…”
Section: Discussionmentioning
confidence: 80%
“…[ 9 10 11 ] Despite these achievements, the household coverage remains well under the target of 90% which is necessary to eliminate IDDs. [ 12 ] Studies done in various parts of India and West Bengal, indicate that consumption of adequately iodized salt in different areas is not universal. [ 13 14 ] This gap in the utilization of adequately iodized salt may be due to non-availability at affordable cost, poor knowledge of iodine deficiency diseases and/or faulty storage practices.…”
Section: Introductionmentioning
confidence: 99%